Evaluation of oxidative stress status and antioxidant defense status of athletes after inclusion of a special product for sportive nutrition in their food ration - R. Rakhmanov; T. Blinova; L. Strakhova; S. Kolesov; V. Troshin; R. Hyairov (National Electronic Information Consortium (NEICON), 2020)
Objective: to evaluate the influence of special «product for sportive nutrition» on oxidative stress status and antioxidant defense status of athletes during physical loads. Materials and methods: 30 male swimmers of a student combined team (at the age of 23,0 ± 2,5 years) participated in the study. The sportsmen were divided into two groups: experimental and control. The sportsmen of experimental group additionally received the «product for sportive nutrition» in their food ration. The training process was the same in both groups; it was divided into three stages. First and third stages were characterized by systematic trainings; the intensity of physical loads was increased at second stage. The oxidative stress status and total antioxidant capacity (TAC) of serum were detected using reagent kit «PerOx (TOS/TOC) Kit» и «ImAnOx (TAS/TAC) Kit», firm «Immundiagnostik» (Germany). Serum cortisol was determined by immunoenzyme method with the use of reagent kit of joint-stock company «Vector-Best» (Russia). Results: intake of «product for sportive nutrition» during increased physical loads promoted a statistically significant decrease of oxidative stress level, tendency to a decrease of cortisol content and an increase of serum antioxidant capacity in comparison with control group. There was no correlation between cortisol value and oxidative stress level/total antioxidant capacity of serum. Conclusions: tested food product exerted a positive influence on system of free radical oxidation and cortisol. It can be recommended for further investigation in persons going in for sport.